Pentingnya Media Sosial Untuk Meningkatkan Kemampuan Berpikir Kritis Dan Kemampuan Pemecahan Masalah - Purwanti Purwanti; Siti Nurhayati (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
In the digital era, social media has become an important element in people's lives. Platforms such as Facebook, Instagram, Twitter, and TikTok no longer only function as a means of communication and social interaction, but also as a medium for obtaining and disseminating information. This condition opens up new opportunities to utilize social media in the field of education and skill development, such as critical thinking skills and problem-solving skills. This article presents a theoretical and empirical analysis of the impact of social media on these two skills, as well as providing recommendations for the productive use of social media in education and self-development. The results of the study show that social media, if used wisely, can be an effective tool for improving complex cognitive skills.